Regression Analysis of the Impact of Foreign Direct Investments, Adjusted Net Savings, and Environmental Tax Revenues on the Consumption of Renewable Energy Sources in EU Countries - Kukharets, Valentyna; Čingiene, Rasa; Juočiūnienė, Dalia; Kukharets, Savelii; Blažauskas, Egidijus; Szufa, Szymon; Muzychenko, Andrii; Белей (Belei), Cвітлана (Svitlana); Лагодин, Назар; Hutsol, Taras (My University, 2024)
It is very important for EU countries to achieve energy independence. But this is actually impossible without a high level of use or consumption of renewable energy (RE) sources. Important parameters affecting the consumption of RE sources are as follows: foreign direct investments (FDI), adjusted net savings (ANS), and environmental tax revenues. In the presented work, the likely impact of the above indicators on the level of use of RE sources was estimated using a second-order regression equation. As a result, it was established that the growth of the adjusted net savings indicator and an increase in environmental tax revenues (ETR) have a positive effect on the level of use of RE sources. With significant FDI, the level of ANS does not have a very obvious effect on the growth of the level of use of RE sources. An increase in the level of ANS allows for an increase in ETR, which in turn contributes to an increase in the level of consumption of RE sources. It was also established that an increase in the level of ANS contributes to a more complete realization of the potential of FDI for the development of RE. It has been empirically established that a consistently high consumption of renewable energy sources is actually possible in the countries with a high level of adjusted net savings, high environmental tax revenues, and active attraction of foreign direct investments
Regression Analysis of the Impact of Foreign Direct Investments, Adjusted Net Savings, and Environmental Tax Revenues on the Consumption of Renewable Energy Sources in EU Countries
Keywords: energy independence; regression equation; coefficients; parameters; indicators